peran aliansi nelayan natuna dalam menghadapi konflik - bhaskara, muhammad surya; Panji Suwarno; Agus Adriyanto; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
This research examines the dynamics of conflict between Natuna fishermen, who use traditional fishing gear, and non-local fishermen who tend to use modern fishing equipment in the seas of Natuna. Natuna fishermen often face violations of their fishing grounds by non-local fishermen, leading to tensions in the area. This conflict is also influenced by economic competition, regulatory ambiguity in the fishing industry, and uncertainty regarding fishing territory boundaries. The Natuna Fishermen Alliance (ANNA) plays a crucial role in mediating this conflict through communication, dialogue, and coordination with the government. The research methodology employed is a descriptive qualitative approach.The results of this study indicate social and educational changes that emphasize the importance of sustainable fisheries resource management. Stricter regulations in fisheries management in the region are a key factor in resolving this conflict. Although conflicts still occur, solidarity among fishermen and efforts to find solutions continue to be the primary focus in creating a more harmonious environment in the seas of Natuna.